1991
DOI: 10.1111/j.1745-9125.1991.tb01084.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender Bias in the Disposition of Juvenile Court Referrals: The Effects of Time and Location*

Abstract: Theory based on sex role traditionalism predicts a more punishing decision for female than for male offenders, while theory based on chivalry (paternalism) predicts greater leniency by the courts for female offenders. This paper tests these two models using a large sample (36,680) ofjuvenile court referrals in metropolitan, urban, and rural locations spanning a nine-year period. Nonparametric analysis of covariance is used to control for differences in offense, previous contact with the court system, and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 22 publications
1
41
1
Order By: Relevance
“…A shortcoming of the work by Fisher and Doyle-Martin (1981) was the failure to control for the independent effects of the type of charge that led to the initial referral. This omission was critical because decision making might be influenced by the youth's offense (D. Johnson & Scheuble, 1991) and stereotypes may be associated with drug or alcohol offenses that in turn may affect case outcomes (Sampson & Laub, 1993). Leiber (1994) found evidence to support this claim.…”
Section: Prior Researchmentioning
confidence: 85%
See 1 more Smart Citation
“…A shortcoming of the work by Fisher and Doyle-Martin (1981) was the failure to control for the independent effects of the type of charge that led to the initial referral. This omission was critical because decision making might be influenced by the youth's offense (D. Johnson & Scheuble, 1991) and stereotypes may be associated with drug or alcohol offenses that in turn may affect case outcomes (Sampson & Laub, 1993). Leiber (1994) found evidence to support this claim.…”
Section: Prior Researchmentioning
confidence: 85%
“…This second perspective, the chivalry perspective, suggests that male decision makers may treat females more leniently because they are taught by society to protect them, or they may have stereotypical beliefs that make it difficult for them to imagine that females engage in delinquent behavior (e.g., Bishop & Frazier, 1996;D. Johnson & Scheuble, 1991).…”
Section: Summary and Discussionmentioning
confidence: 98%
“…Prior research on the impact of gender on the decision to detain a youth has produced mixed results. While some studies have found that females are treated with leniency compared to their male counterparts (Bishop & Frazier, 1992, 1996Johnson & Scheuble, 1991;McCord et al, 2001), other research has found that females are treated more harshly than males (Bishop & Frazier, 1996;Chesney-Lind, 1977). Several studies have examined the intersection of race and gender on juvenile justice decision-making and have found that while white males and females are treated similarly to one another, African-American females often receive some degree of leniency compared to their male counterparts, which supports the findings in the current study (Leiber & Johnson, 2008;Rodriguez, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…This omission is critical because past studies show that decision making may be influenced by the youth's offense (Johnson and Scheuble 1991). Also, stereotypes associated with drug or alcohol offenses have been found to affect the likelihood of receiving either harsher or more lenient outcomes in criminal and juvenile court proceedings (Farnworth et al 1991;May 1982aMay , 1982bMoore et al 1978;Robbins 1984;Winfree, Griffiths, and Sellers, 1989;Zatz 1984).…”
Section: Past Researchmentioning
confidence: 96%